Advances in artificial intelligence : 26th Canadian Conference on Artificial Intelligence, Canadian AI 2013, Regina, SK, Canada, May 28-31, 2013. Proceedings - Zilles, Sandra; Zaiane, Osmar R. (Lecture Notes in Computer Science, 2013)
This book constitutes the refereed proceedings of the 25th Canadian Conference on Artificial Intelligence, Canadian AI 2012, held in Regina, SK, Canada, in May 2013. The 17 regular papers and 15 short papers presented were carefully reviewed and selected from 73 initial submissions and are accompanied by 8 papers from the Graduate Student Symposium that were selected from 14 submissions. The papers cover a variety of topics within AI, such as: information extraction, knowledge representation, search, text mining, social networks, temporal associations.